A Case of Oxalate Nephropathy in a Known Diabetic Patient following Acute Alcoholic Pancreatitis. (19th July 2022) - Odhiambo, John; Patel, Hanika; Mutuiri, Anderson; Yakub, Fazal; Sokwala, Ahmed
Abstract : This was a case of a 39-year-old gentleman known to have diabetes mellitus since February 2021 on insulin glargine (Lantus) 16 units nocte and sitagliptin/metformin 50/500 mg once a day who presented to a tertiary teaching hospital in Kenya in May 2021 with a three-week history of vomiting and diarrhea. He had been previously admitted to a different facility with acute alcoholic pancreatitis. His examination was nonremarkable except for mild dehydration and pallor. He had moderate metabolic acidosis and deranged renal function. Prior to this, his creatinine was normal. As part of the evaluation for the rapid deterioration of renal function, a kidney biopsy performed revealed oxalate nephropathy. He was started on renal replacement therapy with hemodialysis.